Talent Management Strategies and Customer Delight : A Conceptual Study - Maben, Annette Sonia; Uchil, Rashmi (Indian Journal of Marketing, 2019)
Managing talents of individuals has always been a challenge for business leaders. Delighting and engaging customers is also a key challenge faced by organizations in order to be competitive and sustain in the global market. This paper tried to analyze the concepts of talent and talent management for organizations. This paper developed a conceptual framework and aimed to review the various strategies for effective talent management and understanding its implications. It is an interdisciplinary approach in which strategic talent management is linked with organizational outcomes of customer delight. It tries to bring in an overall approach in terms of means and ends, the ends being customer delight. This paper tried to provide insights on concepts, strategies, and implications of talent management practices required for further empirical research.